Neuroimaging in multiple sclerosis. - Noseworthy, J; Paty, D; Ebers, G (1984)
Conventional CT studies were the first neuroimaging tools shown to be frequently useful in the assessment of patients with multiple sclerosis. The most commonly noted abnormalities are cerebral atrophy, foci of decreased density, and contrast enhancing lesions. Hypodense lesions may represent either recent or remote sites of demyelination and this can be determined in part by the response of these abnormalities to contrast administration and by their evolution with serial CT studies. There is compelling evidence that CT enhancing lesions correspond to sites of active inflammation and demyelination. High-volume delayed CT studies increase the number of CT abnormalities seen, particularly in patients examined at the time of clinical disease activity. These studies appear to be well-tolerated in properly hydrated patients with normal renal function. NMRI studies appear to be the most sensitive way to detect MS lesions and are particularly useful in demonstrating abnormalities in the posterior fossa. Less is known of the pathologic substrate and the evolution of these NMR abnormalities. It appears likely that NMR detected lesions usually do not resolve completely and consequently changes seen with this neuroimaging technique may represent the cumulative effects of past and present disease activity.